Remdesivir Inhibits Tubulointerstitial Fibrosis in Obstructed Kidneys - Xu, Lin; Tan, Bo; Huang, Di; Yuan, Meijie; Li, Tingting; Wu, Ming; Ye, Chaoyang (Frontiers in Pharmacology, 2021)
Aim: Kidney impairment is observed in patients with COVID-19. The effect of anti-COVID-19 agent remdesivir on kidneys is currently unknown. We aimed to determine the effect of remdesivir on renal fibrosis and its downstream mechanisms. Methods: Remdesivir and its active nucleoside metabolite GS-441524 were used to treat TGF-β stimulated renal fibroblasts (NRK-49F) and human renal epithelial (HK2) cells. Vehicle or remdesivir were given by intraperitoneal injection or renal injection through the left ureter in unilateral ureteral obstruction (UUO) mice. Serum and kidneys were harvested. The concentrations of remdesivir and GS-441524 were measured using LC-MS/MS. Renal and liver function were assessed. Renal fibrosis was evaluated by Masson’s trichrome staining and Western blotting. Results: Remdesivir and GS-441524 inhibited the expression of fibrotic markers (fibronectin and aSMA) in NRK-49F and HK2 cells. Intraperitoneal injection or renal injection of remdesivir attenuated renal fibrosis in UUO kidneys. Renal and liver function were unchanged in remdesivir treated UUO mice. Two remdesivir metabolites were detected after injection. Phosphorylation of Smad3 that was enhanced in cell and animal models for renal fibrosis was attenuated by remdesivir. In addition, the expression of Smad7, an anti-fibrotic factor, was increased after remdesivir treatment in vitro and in vivo. Moreover, knockdown of Smad7 blocked the antifibrotic effect of GS and RDV on renal cells. Conclusion: Remdesivir inhibits renal fibrosis in obstructed kidneys.